Pemanfaatan Botol Plastik dengan Menggunakan Sistem Hidroponik - Vincent Vincent; Noviana Noviana; Ora Chintya; Selly Julianti; Yoel Yoel; Angeline Angeline; Herwin Herwin; Ilham Andika (National Conference for Community Service Project (NaCosPro), 2019)
The purpose of this article is to discuss making a product that can facilitate people whose agricultural land is limited to grow vegetables. The hydroponic planting method is a method of planting plants without using growing media from the soil. By using the hydroponic method and plastic bottles as planting containers, it will be easier for people to get vegetables. Hydroponic advantages include, more efficient land use, higher quantity, and quality of production and cleaner, easier pest and disease control, Water requirements in hydroponics are less than water requirements in aquaculture with soils.